PENGHARAPAN DI TENGAH PANDEMI COVID-19 - Adri Onyong Engelberd Matinahoruw (STT BIBLIKA JAKARTA, 2021)
The world is faced with quite a serious problem. This problem is the Corona Virus outbreak or better known as Covid-19. This plague then made many people worry and fear because many had died as a result of the plague, and this then raised many questions both medically, ethically but also rationally, and of course including raising questions to believers, where is Allah in live with the current conditions. In this article, we will discuss how believers can do theology or in other words feel the presence of God in the midst of this Covid-19 situation by using a qualitative approach to literary studies. The data source referred to is all information in the form of real objects, events. What is interesting in this article is what kind of God can be felt in the conditions of the Covid-19 outbreak.